Novel Castellaniella denitrificans SA13P as a Potent Malachite Green Decolorizing Strain - Ankita Chawla; Baljeet Singh Saharan (Applied and Environmental Soil Science)
Triphenylmethane dyes represent a major group of dyes causing serious environmental hazards. Malachite Green is one of the commonly and extensively used triphenylmethane dyes although it is carcinogenic and mutagenic in nature. Various physicochemical methods have been employed for its elimination but are highly expensive, coupled with the formation of huge amount of sludge. Hence, biological methods being ecofriendly are good alternatives. In the present study, the novel bacterial isolate SA13P was isolated from UASB tank of tannery effluent treatment plant. Phylogenetic characterization of 1470 bp fragment of SA13P has revealed its similarity with Castellaniella denitrificans. This strain has been found to decolorize the dye (malachite green) at a concentration of 100 mg L−1 (80.29%). Decolorization was done by living bacterial cells rather than adsorption. Growth conditions have also been optimized for the decolorization. Maximum decolorization was observed at a temperature of 37°C and pH 8.0. Also, it has been found that bacterization of seeds of Vigna radiata with Castellaniella denitrificans SA13P increases germination rate. We have reported for the first time that Castellaniella denitrificans SA13P may be used as a novel strain for dye decolorization (malachite green) and biological treatment of tannery effluent.